"Many Ghosts To Fight, Many Prejudices To Overcome" - Aghacy, Samira (1997)
When asked by the Institute for Women's Studies in the Arab World to write an introductory article (on the short stories written by Lebanese women since 1960) to a "Bibliography of Lebanese Woman's Writing," I did not hesitate despite many other responsibilities. Starting off, I had expected a handful of stories, but I began to discover that the number of stories as well as novels written by women is considerable. I found out that with the exception of few writers, the bulk of women's writing is virtually unknown to the reader despite the sound quality of many of their works.